Evaluation of the child-friendly school policy in indonesia: analysis of effectiveness and implementation challenges - Aziz, Hafidh; Sudrajat, Ajat; Suparno, Suparno; Pashela, Perdana; Azzahra, Laras Putri; Mannana, Nadaina Fadhila (Intelektual Pustaka Media Utama, 2025)
This study aims to explore in greater depth the role of implementing child-friendly schools, parental involvement in enhancing the effectiveness of child-friendly school policies and practices, and evaluating the challenges that arise in the implementation of child-friendly schools. This qualitative descriptive exploratory research utilizes the content analysis method. Purposive sampling was used to select five teachers, including the headmaster, three parents, and forty-seven students who participated in this study. Data was collected through semi-structured interviews and non-participant observations to explore the policy and practice of the child-friendly school, focusing on affectiveness and challenges in the teaching and learning process. The research results highlight the importance of a comprehensive and inclusive approach to early childhood education (ECE) to support the effectiveness of child-friendly schools, as well as the importance of ongoing evaluation, adaptation, and collaborative efforts in implementing and maintaining child-friendly schools in globally quality ECE efforts. The implications of this study offer valuable insights for educators, policymakers, and researchers in improving and adjusting the child-friendly school model in various educational settings. This study contributes to the evolving discourse on child-friendly schools by providing understanding about the successes and challenges faced in a specific context.